PENDAPATAN DAN TINGKAT KESEJAHTERAAN PETANI LADA DI KECAMATAN GUNUNG LABUHAN KABUPATEN WAY KANAN - Saut M Togarotop; Dwi Haryono; Novi Rosanti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research aims to determine the pepper farmers income in the Gunung Labuhan Sub District, Way Kanan District, the welfare level of  pepper farmers in the Gunung Labuhan Sub District, Way Kanan District.The location was selected deliberately (purposive). Data retrieval was implemented in July 2013 to August 2013. Data used in this research were primary and secondary data. The number of samples in this research were 63 farmers, from the Way Tuba Village and Gunung Sari Village, selected by using simple random method. Data processing was performed using quantitative methods to calculate the household incomes of farmers, and qualitative descriptive methods to know the welfare level of  pepper farmers. The results of this reasearch indicated that  pepper farmers income amounting to 32.20 percent of total household income, with an average income of Rp9,841,199,- per year, based on the criteria of BPS households pepper farmers in Gunung Labuhan Sub District, which included in the category prosperous  as many  as 95.2 percent and the remaining 4.8 percent of households in Gunung Labuhan Sub District included in the not prosperous category. Keywords : farmers, farming, income, pepper, welfare